Comparison of Compression Parallel to Grain of Acacia Hybrid for Untreated and Treated at Different Combination of Age Groups - Gaddafi ISMAILI; Mohamad Yakub BIBI SURIANI; Iskanda OPENG; Nur Syahina YAHYA; Ismaili ZURINA (Medžiagotyra)
Sarawak's wood-based industries face challenges due to a shortage of wood-based raw materials. Research on the Acacia hybrid species is limited, but it is crucial for the timber engineering field. Acacia hybrids have been selected for reforestation projects due to their rapid growth. Since 2001, various license holders have planted Acacia mangium and its hybrids on over 245,000 hectares in Sarawak. The species were collected from a plantation area owned by Daiken Sarawak Sdn Bhd. Tests on physical properties, namely moisture content (MC) and basic density, were carried out. Meanwhile, tests on mechanical properties for both untreated and treated samples were also conducted, including static bending tests (modulus of rupture, MOR and modulus of elasticity, MOE) and compression parallel to the grain test. All the tested samples were in air-dry condition, with the MC ranging from 12 % to 19 %. The specimens were prepared according to BS 373:1957 and Method of Testing Small Clear Specimens of Timber. All tested results were analyzed using statistical methods to determine mean results. All the results that had been tested were analyzed using statistical analysis as mean results. Comprehensive testing of Acacia hybrid wood treated with copper chrome arsenic (CCA) has significantly improved its physical and mechanical properties. The treatment results in higher density and strength, influenced by growth and structural variations of the wood. It also enhances moisture retention, boosting the wood's hydrophobic properties and durability. Treated wood shows increased Modulus of Rupture (MOR) and Modulus of Elasticity (MOE) in static bending tests, demonstrating enhanced resistance to bending and structural integrity. Compression tests reveal that treated wood is 27% stronger than untreated, confirming its superior ability to withstand compressive forces. From this study, the best age combination product is 10y+10y, and it can be concluded that the comprehensive testing of Acacia hybrid wood reveals treatments enhance its physical and mechanical properties.